Second Screen Engagement of Event Spectators - Tomas Cerny; Michael Jeff Donahoo (Advances in Human-Computer Interaction)
An effective means of engaging spectators at live events involves providing real-time information from a variety of sources. Consumers demand personalized experience; thus, a single channel perspective fails. Modern entertainment must extend to spectator mobile devices and adapt content to individual interests. Moreover, such systems should take advantage of venue screens to engage in sharing live information, aggregated social media, etc. We propose a second screen application, providing each audience member a personalized perspective, involving mobile devices equipped with Wi-Fi, and spanning to venue screens in hotels, halls, arenas, elevators, etc. Such a system engages both local audience and remote spectators. Our work provides a case study involving experience from the deployment of such an application at the ACM-ICPC World Finals with audiences at the event and around the world. We analyze and categorize its features, consider its impact on the audience, and measure its demands.